The Relationship Between HIV/AIDS Knowledge and Dating Behavior Among Senior High School Students - Mia Listia; Putri Tresna (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
The WHO reported that approximately 39.0 million people were living with HIV at the end of 2022, with 1.3 million new infections and 630,000 deaths due to HIV-related illnesses in the same year. One of the factors contributing to risky dating behavior among adolescents is a lack of knowledge about HIV/AIDS, leading to limited understanding of its consequences. This study aimed to analyze the relationship between HIV/AIDS knowledge and dating behavior among eleventh-grade students. A quantitative descriptive correlational method with a cross-sectional approach was used. The sample consisted of 70 respondents selected through purposive sampling. The research instruments included the HIV-KQ-18 questionnaire and the SBQ, both of which have been tested for validity and reliability. The results showed that 17.1% of respondents had low knowledge levels, while 18.6% engaged in risky dating behaviors. The Spearman’s rho test indicated a significant relationship between HIV/AIDS knowledge and dating behavior (p = 0.000; r = 0.697). Thus, there is a strong and positive relationship between HIV/AIDS knowledge and adolescent dating behavior. These findings imply the need for structured reproductive health education programs in secondary schools, such as regular counseling sessions and integration of HIV/AIDS content into the curriculum, to reduce risky dating behaviors among adolescents.